Gas-phase VUV photoionisation and photofragmentation of the silver deuteride nanocluster [Ag10D8L6]2+ (L = bis(diphenylphosphino)methane). A joint experimental and theoretical study1. Issue 39 (21st October 2015) - Daly, Steven; Krstić, Marjan; Giuliani, Alexandre; Antoine, Rodolphe; Nahon, Laurent; Zavras, Athanasios; Khairallah, George N.; Bonačić-Koutecký, Vlasta; Dugourd, Philippe; O'Hair, Richard A. J.
<x xml:space="preserve">Abstract</x> The VUV photoionisation and photofragmentation of a mass-selected, ligated silver deuteride nanocluster was studied.